Formação em Adorno e Horkheimer - Santana, Icaraí Daiane (2014)
This work‟s object of study is the concept of formation in the perspectives of T. W. Adorno and Max Horkheimer, and it tries to understand the difficulties and the possibilities of a project of cultural formation (bildung) taking into consideration the context in which the individual constitutes and humanizes himself. In order to do so, we have resorted to bibliographic research. Reflecting about the matter of formation is a crucial task to turn educational activity into an education that forms autonomous, ethical subjects that can contribute to the creation/rescue of values that dignify men. The bildung is a polysemic concept that reaches the political, economic, social and cultural aspects that determine it. It requires reflection about it, about its limits and about its social determinants and denounces the exploitation of reason and formation. It is essential, in this discussion, that we apprehend the following categories: reason (subjective and objective), semi-formation (haldbildung) and formative experience, enlightenment and individual. Such concepts are made explicit in the critical theory of the "Frankfurt School" when they analyze the constitutive nexus that shape the capitalist society and the implications for formation. Adorno and Horkheimer denounce that the thinking and the effective practice for formation are obstructed by the domination of instrumental rationality that is deep-seated in all aspects of social life. They indicate elements and principles in the perspective of a formation leading to autonomy and critical thinking, as well as the limits of the current notion of formation and its nature of adaptation, reproduction and maintenance of the social conditions in vigor, turning into semi-formation.